The development and experimental research of a cryogenic internal cooling turning tool. (15th October 2021) - Gan, Yongquan; Wang, Yongqing; Liu, Kuo; Wang, Siqi; Yu, Qingbo; Che, Chang; Liu, Haibo
Abstract: The cutting ﬂuids used in machining are causing environmental pollution and endanger the health of workers. Liquid nitrogen is non-toxic, harmless, and environmentally friendly. Using liquid nitrogen as a cryogenic cooling medium for cutting is an environmentally friendly and sustainable green machining method, which can effectively reduce cutting temperature and improve the machining quality. However, compared with internal cooling, the flood cooling method consumes significant volumes of liquid nitrogen and shortens tool life. Therefore, it is necessary to develop a kind of turning tool to realize liquid nitrogen internal cooling. In the present work, the relationship model of the jet micro holes size and injection length was established. The reasonable injection distance and hole position of the jet was quantitatively analyzed. A novel liquid nitrogen internal cooling turning tool was developed to reduce the influence of the Leidenfrost phenomenon. And the temperature loss of the turning tool is only 5‰. The surface morphology, surface roughness and tool wear of Ti–6Al–2Zr–1Mo–1V alloy (TA15) were analyzed under three cooling conditions: cutting ﬂuid(wet), liquid nitrogen flood cooling and liquid nitrogen internal cooling. The results show that the liquid nitrogen internal cooling has higher cooling efficiency, which can effectively improve the surface quality and reduce the tool wear. In terms of surface quality, under liquid nitrogen internal cooling condition, the machined surface roughness (Ra) can be increased by 28% at most. Compared with liquid nitrogen flood cooling, the tool wear is reduced by 34% at most. Overall, for hard-to-cut materials, liquid nitrogen internal cooling is a viable option to realize clean production.